2021
DOI: 10.2147/ijgm.s336105
|View full text |Cite
|
Sign up to set email alerts
|

Immune Score Indicator for the Survival of Melanoma Patients Based on Tumor Microenvironment

Abstract: Background Tumor microenvironment (TME) refers to the cellular environment where tumors exist, including immune cells, fibroblasts, stromal cells, chemokines, etc. TME is closely related to the prognosis of various tumors; nevertheless, limited studies have established predictive prognosis models based on TME. This work aims to construct a survival prediction model for melanoma patients based on TME. Methods Data of 482 melanoma patients were extracted from The Cancer G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Compared with the low FerrGR group, the high FerrGR group had a higher immune score and higher tumor purity. Generally, immune scores increased significantly with the malignant progression of SKCM ( Ning et al, 2021 ), while tumor purity decreased at higher grades in our analysis. Immune cells constitute a comfortable environment for tumor growth, suggesting that the poor prognosis of patients in the high FerrGR group is due to the tumor immunosuppressive environment (TIME).…”
Section: Discussionmentioning
confidence: 52%
“…Compared with the low FerrGR group, the high FerrGR group had a higher immune score and higher tumor purity. Generally, immune scores increased significantly with the malignant progression of SKCM ( Ning et al, 2021 ), while tumor purity decreased at higher grades in our analysis. Immune cells constitute a comfortable environment for tumor growth, suggesting that the poor prognosis of patients in the high FerrGR group is due to the tumor immunosuppressive environment (TIME).…”
Section: Discussionmentioning
confidence: 52%
“…The goal of this algorithm was to retrieve stromal, immune and estimate scores. In particular, both stromal and immune scores were positively correlated to infiltration of stromal and immune cells, while the estimate score (the sum of the stromal and immune scores) was a negative indicator of purity of tumor cells (32). Compared with the low-risk group, the high-risk group with lower immune/stromal/estimate score exhibited higher tumor purities (Figure 7B).…”
Section: Analysis Of Immunological Status and Tme Characterizationmentioning
confidence: 94%
“…Additionally, FGD3, FGD4 also been found to modulate actin cytoskeletons and exchange CdC42-Specific factors (14,15). According to FGD2, studies have shown that it affects the prognosis of melanoma patients and high expression of it in HNSCC may improve patients' prognosis (11,16). Besides, FGD2 has the ability to positively regulate immune cell infiltration in LUAD (17).…”
Section: Introductionmentioning
confidence: 99%